Liudi pobedy : Ni shagu nazad! - Lazebnik, Olga; Legeida, Elena (Ukraine, 2018)
The film is dedicated to the heroes of the most atrocious and bloody war in the history of mankind.
Verzio Film Festival Submission
Keywords: Documentary films